2020
DOI: 10.1038/s41598-020-74396-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dens invaginatus in young Israeli population and its association with clinical morphological features of maxillary incisors

Abstract: Dens invaginatus is an anomaly mostly observed in maxillary incisors. This study aimed to assess the prevalence of dens invaginatus in maxillary incisors in young Israeli population and to study its potential association with clinical coronal morphological features. Data was collected from periapical radiographs and clinical photographs of patients from Orthodontics Department between 2006 and 2018. Radiographic characteristics were evaluated and compared to clinical coronal morphological features. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…In the present study, DI affected both sexes equally, which is consistent with the findings of previous studies 3 , 5 , 6 , 11 , 13 , 15 . However, other studies have found males to be more affected 4 , 14 .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, DI affected both sexes equally, which is consistent with the findings of previous studies 3 , 5 , 6 , 11 , 13 , 15 . However, other studies have found males to be more affected 4 , 14 .…”
Section: Discussionsupporting
confidence: 94%
“…In a sample of Saudi patients, DI was detected in 10% of the patients 17 . A higher value (37%) was recently reported in an Israeli population 13 . These variations may be related to different ethnic groups, methods of assessment, and/or diagnostic criteria.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations